PENGGUNAAN BATTRA PIJAT DALAM PENYEMBUHAN PENYAKIT (Studi Perilaku Pencarian Pengobatan Lima Pasien Panti Pijat KUBE Dharma Bakti ) - Paramarta, Putu Satya Manggala; Zuryani, Nazrina; Astika, Ketut Sudhana (JURNAL ILMIAH SOSIOLOGI (SOROT), 2016)
ABSTRACT The advanced of knowledge and technology in health, had impact in advance of medicinal treatment. However the advanced of medicinal treatment didn’t entire drag traditional treatment (Battra) in society. Battra Pijat at Panti Pijat Tuna Netra KUBE Dharma Bakti Denpasar wasone of Battra was still became interest in society. Based on the fact this research guided for understanding the behaviour health on Battra Pijat at Panti Pijat Tuna Netra KUBE Dharma Bakti Denpasar can be formulated as follows 1) How the implemented of Battra Pijat at Panti Pijat Tuna Netra KUBE Dharma Bakti? and 2) How the health seeking behaviour of five patient at Panti Pijat Tuna Netra KUBE Dharma Bakti ? The theory of Rossenstock used for answer of the problem, with the qualitative approach. The results of the research conducted in Battra Pijat at Panti Pijat Tuna Netra KUBE Dharma Bakti Denpasar were: the threated from family and the factor from the outside from individual such as from family, friend, media, and hospital medicinal behaviour, became the individual motivator to did the medicinal in PantiPijat Tuna Netra KUBE Dharma Bakti. The payment risk and the disease which could be serious couldn’t be compared with the benefit which the individual felt who had treatment in Panti Pijat Tuna Netra KUBE Dharma Bakti among others without medical procedure, didn’t use the medicine, could compare with another medicine, the medicinal, good interaction between terapist and patient could be motivate the individual easily. The conclusion of the study was the search Battra Pijat on Panti Pijat Tuna Netra KUBE Dharma Bakti behaviour by society influenced by the beliefof the search medicinal treatment was better than the others medicinal treatment. Key words: Health Seeking Behavior , Battra Pijat